1990
DOI: 10.1021/bi00463a030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cDNAs of the human pregnancy-specific .beta.1-glycoprotein family, a new subfamily of the immunoglobulin gene superfamily

Abstract: Three highly homologous cDNAs encoding human pregnancy-specific beta 1-glycoprotein (SP1) were isolated from a human placental cDNA library. These cDNAs share greater than 90% nucleotide homology in their coding sequences, and greater than 79% of the encoded amino acids are homologous. Proteins encoded by these cDNAs are very similar to members of the carcinoembryonic antigen family and contain repeating domains, conserved disulfide bridges, and beta-sheet structure typical of the immunoglobulin gene superfami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…A recent report by Zheng et al (1990) indicates that our PSGlO cDNA is virtually identical in sequence with their hPSl2 cDNA, and their finding of the corresponding mRNA ADDED IN PROOF in placenta is consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 92%
“…A recent report by Zheng et al (1990) indicates that our PSGlO cDNA is virtually identical in sequence with their hPSl2 cDNA, and their finding of the corresponding mRNA ADDED IN PROOF in placenta is consistent with the results reported here.…”
Section: Discussionsupporting
confidence: 92%
“…Sequence analysis from nucleotides -150 to -124 between members of the PSG family showed that the 27-bp sequence reported here is very similar to those of other PSG 5' flanking regions (e.g. PSG12 and PSG3) [34, 361. In addition, the farthest 5' transcription start site described for PSGl [13] is also located within the 27-bp sequence. Some TATA-box-less genes initiate their transcription through pyrimidine-rich initiator elements which are often located overlapping the cap site [17], though the positions of the initiator elements are not necessarily fixed and may be found distal to the initiation site [37].…”
Section: Discussionmentioning
confidence: 99%
“…FL17b PSG4 (57), hPS133', PSG9 (PS,,) (63,103) PSG5 (61), PSPG HL (clone 12-2) (60) FL-NCA-3 (55) PSpG HL (clone 22) (60) hsCGM3 (42). FL26b, PSGGB (69) PSG6 (57) hPS12 (58), PSGlO(103) PSG7 (61)a.b.d CGM35 (59), PSG8' hTSl (1 18) PS34 (222), PSPC-Ge, PSPG B (37), PSG7 (223) hPS2 (58), hPS91' 11' 18' PSG14b been determined so far with some certainty, i.e., through comparison of the N-terminal domain sequences. For PSG 12 and PSGl3, this information is lacking as sequence data only exists from internal domains for these genes.…”
Section: Size Of the Human Cea Gene Familymentioning
confidence: 99%